Experimental study on the fiber pull-out of composites using digital gradient sensing technique. (February 2015) - Hao, Wenfeng; Tang, Can; Yuan, Yanan; Yao, Xuefeng; Ma, Yinji
Abstract: A method to measure the stress field at the fiber tip in the fiber pull out test was proposed by using a digital gradient sensing technique. First, the principle of digital gradient sensing is introduced, and the non-contact optical system of digital gradient sensing developed. Then, a fiber reinforced composite model specimen, where a nail was inserted in epoxy resin to act as a fiber, was performed, and a pull out test was conducted on the specimen using the digital gradient sensing technique. Finally, the angular deflections contour at the fiber tip was obtained, and the stress intensity factor was extracted from the angular deflections. The results show that the stress intensity factor at the fiber tip extracted from the angular deflections agreed with the results calculated by the finite element method.